ANALISIS PENINGKATAN KESELAMATAN PENGGUNA JALAN PADA DAERAH RAWAN KECELAKAAN JALAN MOAN SUBU-JALAN SOEKARNO HATTA - Maria Elisabeth Botu; Anastasia Merdekawati Noralita Soludale (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2024)
In public transportation systems, safety is an essential consideration for users, both for their safety and for the safety of others in their vicinity (Bolla et al., 2013). Traffic accidents encompass collisions and loss of vehicle control occurring on roads, resulting in injuries or fatalities to individuals as well as damage to property, involving at least one motor vehicle (Sugiyanto and Santi, 2015). The objectives of this study were to identify the factors contributing to traffic accidents in accident-prone areas and to explore strategies for mitigating accident risks or improving conditions to reduce accident rates on Moan Subu Road and Soekarno Hatta Road. This research employed a quantitative approach using survey methods, distributing questionnaires to 100 respondents from the surrounding community. Data processing in this study utilized descriptive statistics. The analysis revealed that the most influencing factors of road user safety were pedestrians (25%), environmental conditions (7%), and drivers (3%). Efforts to enhance road safety at the research location include short-term interventions such as reaffirming road markings, improving street lighting, addressing problematic parking on roadways, enhancing pavement quality, and providing facilities for pedestrians.